Keeping You in the Know: A Novel Approach to Journal Article Evaluation and Presentation for the Perioperative Team - MacDonald, Kathy (Operating Room Nurses Association of Canada Journal, 2020)
The children’s Operating Room at the IWK Health Centre in Halifax, NS, has had some form of a journal club in place for the perioperative nursing group for, off and on, the past twenty years. At times the journal club has had strong participation from the nursing team and, at other times, involvement has been low. This article includes a literature review on the subject of journal clubs and goes on to review the approaches that have worked in our setting. It also discusses the challenges that have been encountered. Participation in the journal club has opened doors for some perioperative nurses and this article aims to assist other perioperative nurses with developing and sustaining a journal club in their setting.